Self-Evaluation of University Teachers’ Digital Competence in Emergency Remote Teaching and Their Emotions Surrounding Student Crisis E-Learning During The 2020 Pandemic - Katarzyna POTYRALA; Lukasz TOMCZYK; Nataliia DEMESHKANT; Karolina CZERWIEC; Wioletta SKRZYPEK (Communications of International Proceedings, 2021)
The main aim of the research was focused on the self-assessment of university teachers’ level of digital literacy (DL) and on the emotions accompanying them during crisis e-learning & teaching during the period of the pandemic in 2020. The research was carried out via online questionnaire (with responses along a 7-point Likert scale) among university teachers (94) at the largest Polish pedagogical university. The research sought to answer the following: what is the level of digital competence of teachers and to what extent is it related to the emotions accompanying them during remote education (according to the teachers' own assessment)? The results offer the conclusion that the respondents appreciated the opportunity to develop their initially low digital skills during the period of crisis remote teaching and they perceive their emotions as being mostly positive during the second wave of Covid-2019. This is in stark contrast to the findings obtained during the first wave of the pandemic described in the current literature. There is evidence here of a coping strategy which allowed the teachers to adapt to the crisis circumstances and to use the time for professional development. In the light of the results obtained, it can be concluded that positive emotions related to the development of university teachers’ digital skills during the pandemic can serve as an effective tool for regulating negative emotions and can influence the attitudes of teachers and students whose education is disrupted by stressful periods such as a pandemic.
Keywords: emergency remote teaching and learning; crisis e-learning; university teachers; digital literacy; emotions; self-evaluation.